2016
DOI: 10.1093/asj/sjv213
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Body Dysmorphic Disorder Symptoms and Body Weight Concerns in Patients Seeking Abdominoplasty

Abstract: Candidates for abdominoplasty had a high prevalence of BDD symptoms, and body weight and shape concerns were associated with increased symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…This is consistent with the results of Brito et al . [ 24 ] In their study in Brazil on the prevalence and severity of body dysmorphic disorder symptoms in patients seeking abdominoplasty (mean age = 38 years), no statistically significant difference was found between groups with respect to their sociodemographic characteristics including educational level. Regarding household income, birth order, school grade, and school type, no similar study was found to compare them with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of Brito et al . [ 24 ] In their study in Brazil on the prevalence and severity of body dysmorphic disorder symptoms in patients seeking abdominoplasty (mean age = 38 years), no statistically significant difference was found between groups with respect to their sociodemographic characteristics including educational level. Regarding household income, birth order, school grade, and school type, no similar study was found to compare them with our results.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Body image dissatisfaction is higher in females than in males. [ 23 24 ] Adolescent girls' concerns about their body image, due to real or imaginary preoccupation, develop a sense of shame which makes them avoid social situations and thus negatively affects their social and academic performance. Given the physical, psychological, and social consequences of BICs, it is important to identify the factors associated with this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the more severe the symptoms of BDD, the higher the level of concern with body weight and shape. Individuals with BDD having distorted self-perception of body shape or distorted comparative perception of body image were, respectively, 3.67 or 5.93 times more likely to show more severe symptoms of BDD than individual with a more accurate perception [47].…”
Section: Cultural Factorsmentioning
confidence: 97%
“…A higher prevalence is observed among adult women (76% of cases) (25 − 40 years) and patients who report esthetic complaints. 4 , 5 , 6 , 7 , 8 These seek care in search of successive treatments, always dissatisfied with previous results. They adopt compulsive ritualistic behaviors such as looking in mirrors and using makeup or clothes that cover the body.…”
Section: Introductionmentioning
confidence: 99%